The Impact of ESG and Governance Factors on Financial Performance: A Business Development Perspective on Commercial Banks Listed on the Indonesia Stock Exchange - Nabilah, Nur Haliza Zahra; Mangifera, Liana (Yayasan Riset dan Pengembangan Intelektual, 2025)
Currently, the issue of sustainability is one of the focuses for many companies. The application of the principles of environmental sustainability, social responsibility, and good governance is important for organizations to increase profitability. The intent of this study is to examine the influence of ESG and governance variables, especially independent board and board gender diversity, toward financial performance. This study involved the population of commercial banks listed on the Indonesia Stock Exchange during 2018-2022. The sampling technique used is purposive sampling method, resulting in a sample of 13 banks. Data testing using SPSS statistical software. The findings demonstrated that financial performance is significantly impacted by ESG, independent boards, and board gender diversity.